Uses of local African pigs in food and traditional practices in Southern Benin - ADOUKONOU-SAGBADJA, Hubert (My University, 2022)
Local pigs are very important in food and traditional practices in Africa. This study aims to document diverse traditional uses of Local African Pigs in Southern Benin. A transverse and retrospective survey was used for data collection from 420 people which were consumers, butchers, resource persons, and conservators of the tradition. The results showed that pig meat was mainly used for the human diet (98.10%). The majority of consumers were public servants (25%). Pig meat occupied the first rank among meats most consumed (92%), but consumers reported that African local pig’s meat had the best taste. It was consumed under various culinary specialties in specialized restaurants and at home. The pig and its derivative products were also used in customs (72.62%), traditional medicine (52.38%), endogenous religions (35.71%), and occultism (3.1%). Pork meat is the most consumed meat in southern Benin (92%), but according to consumers, meat from the local pig breed is the one that provides the best taste (69.30%). It is consumed under various culinary specialties (boiled, fried, and grilled form) in specialized restaurants as well as in families. Local pig in particular and their derivative products were also used as gifts for many divinities and sacrifices to ward off bad fates and to cure various diseases. Regarding the importance of local pigs in Southern Benin, it is essential to implement strategies for their conservation and sustainable management.
Keywords: Zoogenetic Resources; Sus scrofa domesticus; Pig meat; Diet; Sociocultural practices; West Africa